Genetics of esterase and glutamate oxaloacetate transaminase isozymes in cassava (Manihot esculenta Crantz) - Sarria, Rodrigo A.; Ocampo Nahar, César H.; Ramírez, H.; Hershey, Clair H.; Roca, W. (International Center for Tropical Agriculture, 1993)
Genetic studies of two isozyme loci have been carried out in root tips of eight cassava F1 progenies using polyacrylamide gel electrophoresis. Two loci, esterase-1 (East-1), the most distant cationic region, and glutamate oxaloacetate transaminase-1 (Got-1), the most proximal anionic region, were evaluated among the segregating populations. Est-1 locus has five multiple alleles, including one null allele, and behaves as monomer, with a diploid inheritance pattern with only two alleles presenting each individual. These data were confirmed by esterase characterization of CIAT cassava germplasm bank accessions; a total of 11 different phenotypes representing 15 different genotypes for this locus were demonstrated. Got-1 locus comprises three allels with diploid inheritance. This work provides evidence for a diploid inheritance pattern of the two isozyme loci supporting the allotetraploid nature of cassava. Many other regions of the zimograms are still to be elucidated. This information will be valuable to interpret studies on isozyme fingerprinting of cassava genetic diversity.